EXTRACTION ABSORBTIOMETRIC DETERMINATION OF AMPICYLINE BY OXASINE BASIC DYE NILE BLUE “B” (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Ampicyline interacts with Nile Blue in hydrochloric acid solutions. The formed ion associate could be extracted by the dichlorethane. Maximal extinction is observed at the value of wavelength 640 nm. Optimal acidity of aquans solutions is pH 1.0 by HCl. The optimal quantities of dye is 1.0–1.8 mL of 0.1% solutions. The coefficient of extraction is 88.5%.